2023
DOI: 10.3389/fnut.2023.1150189
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiol treatment improves metabolic profile and decreases hypothalamic inflammation caused by maternal obesity

Abstract: IntroductionThe implications of maternal overnutrition on offspring metabolic and neuroimmune development are well-known. Increasing evidence now suggests that maternal obesity and poor dietary habits during pregnancy and lactation can increase the risk of central and peripheral metabolic dysregulation in the offspring, but the mechanisms are not sufficiently established. Furthermore, despite many studies addressing preventive measures targeted at the mother, very few propose practical approaches to treat the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 146 publications
0
3
0
Order By: Relevance
“…The perinatal obesogenic milieu of maternal obesity leads to hypothalamic inflammation, which is a crucial mechanism for metabolic dysregulation in offspring 10 . Alleviating hypothalamic inflammation with cannabidiol significantly enhanced the peripheral metabolic profile of Wistar rat offspring 32 . A prospective human dual‐cohort study observed an approximately linear association between maternal pre‐pregnancy BMI and offspring hypothalamic microstructure on MRI images, further demonstrating the plasticity of prenatal hypothalamic development in the context of maternal overnutrition during pregnancy 33 …”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The perinatal obesogenic milieu of maternal obesity leads to hypothalamic inflammation, which is a crucial mechanism for metabolic dysregulation in offspring 10 . Alleviating hypothalamic inflammation with cannabidiol significantly enhanced the peripheral metabolic profile of Wistar rat offspring 32 . A prospective human dual‐cohort study observed an approximately linear association between maternal pre‐pregnancy BMI and offspring hypothalamic microstructure on MRI images, further demonstrating the plasticity of prenatal hypothalamic development in the context of maternal overnutrition during pregnancy 33 …”
Section: Discussionmentioning
confidence: 98%
“…10 Alleviating hypothalamic inflammation with cannabidiol significantly enhanced the peripheral metabolic profile of Wistar rat offspring. 32 A prospective human dual-cohort study observed an approximately linear association between maternal pre-pregnancy BMI and offspring hypothalamic microstructure on MRI images, further demonstrating the plasticity of prenatal hypothalamic development in the context of maternal overnutrition during pregnancy. 33 Interestingly, in the present study, the hypothalamic DEGs of offspring with maternal obesity were not only enriched in the physical functions of the hypothalamus (such as neurodevelopment and metabolic hormone regulation) but also in immune system regulation.…”
Section: Maternal Obesity Causes the Hypothalamic Inflammation In Off...mentioning
confidence: 94%
“…It is possible that longer observation times and with higher doses of CBD are necessary to induce measurable changes in body composition. It is also possible that the anti-inflammatory effects of CBD which potentially modulate metabolic regulators in muscle are only observable in preclinical studies [ 46 ]. The effect of long-term CBD consumption on LBM and BF% in humans is understudied and is only addressed in survey-based cannabis research.…”
Section: Discussionmentioning
confidence: 99%